Analisis Kondisi Rumah, Sosial Ekonomi dan Perilaku sebagai Faktor Risiko Kejadian Frambusia di Kota Jayapura Tahun 2007 - R. Indra Boedisusanto, Fajar Waskito, Haripurnomo Kushadiwijaya (Berita Kedokteran Masyarakat (BKM), 2009)
Background:     Yaws  is caused by     spiral bacillus  called  treponema perteneu.  It  is a human  infectious disease which  commonly attacks  skin  and  bones. The  prevalence  of  yaws  in  Indonesia was  less  than  1  per  10,000 people  but  there were places with high  prevalence  such  as Provinces  of West  Papua, Papua, South East  of Sulawesi, Nusa Tenggara Timur  and Maluku. The prevalence  of yaws  in Jayapura Municipality  in  2007 was  5.4 per 10,000  people.Objective: To  identify  risk  factors  of house  condition,  social  economic  factors  and  behavioral  factors  of  the occurence  of  yaws  at Jayapura Municipality.Method: The  study was  observational with  case  control  study  design. Sample  of  the  study  consisted of  84 cases  and  84  control  subjects. Data were  analyzed  using  computer with  2  x  2  tables  and multiple  logistic regression  tests at  95%  significant  level.Result: Multivariable  analysis  showed  that  three  variables were  significant  risk  factors  for  the  occurence  of yaws:  house condition  (occupancy  density, OR=2,5, availability  of  clean water, OR=5.9),  and behavior  (taking a bath, OR=3.8).Conclusion: Factors  of  house  condition  (occupancy  density,  availability  of  clean water),  social  economy (knowledge)  and  behavior  (taking  a  bath)  are  dominant  risk  factors  for  the  occurence  hence  prevalence  of yaws  at  Jayapura Municipality.Keywords: Yaws,  risk  factors,  Jayapura Municipality